Genome-wide functional analysis of Plasmodium protein phosphatases reveals key regulators of parasite development and differentiation. - Guttery, D; Poulin, B; Ramaprasad, A; Wall, R; Ferguson, D; Brady, D; Patzewitz, E; Whipple, S; Straschil, U; Wright, M; Mohamed, A; Radhakrishnan, A; et al. (Cell Press, 2014)
Reversible protein phosphorylation regulated by kinases and phosphatases controls many cellular processes. Although essential functions for the malaria parasite kinome have been reported, the roles of most protein phosphatases (PPs) during Plasmodium development are unknown. We report a functional analysis of the Plasmodium berghei protein phosphatome, which exhibits high conservation with the P. falciparum phosphatome and comprises 30 predicted PPs with differential and distinct expression patterns during various stages of the life cycle. Gene disruption analysis of P. berghei PPs reveals that half of the genes are likely essential for asexual blood stage development, whereas six are required for sexual development/sporogony in mosquitoes. Phenotypic screening coupled with transcriptome sequencing unveiled morphological changes and altered gene expression in deletion mutants of two N-myristoylated PPs. These findings provide systematic functional analyses of PPs in Plasmodium, identify how phosphatases regulate parasite development and differentiation, and can inform the identification of drug targets for malaria.